ТЕСТУВАННЯ ЯК ІННОВАЦІЙНА ТЕХНОЛОГІЯ ОЦІНЮВАННЯ РІВНЯ ЗНАНЬ З ІНОЗЕМНОЇ МОВИ ЗА ПРОФЕСІЙНИМ СПРЯМУВАННЯМ У ФАХОВИХ ДЖЕРЕЛАХ (Innovative professional education, 2022)
The work describes testing as an innovative technology for assessingthe level of knowledge of a foreign language according to a professional direction inprofessional sources. It has been proven that the use of an online electronic surveyimproves the quality of knowledge testing, forms a positive attitude and a positiveattitude towards the academic discipline
Keywords: assessment, test, informatization, teaching of foreign languages, institution of vocational pre-higher education